Malaysian civil procedure 2018 - Ariffin Zakaria; Gopal Sri Ram (Sweet & Maxwell Asia Malaysia, 2018)
The Malaysian Civil Procedure 2018 brings you the must-have court litigation reference that provides illuminating commentary on the new Malaysian Rules of Court 2012. Drawing on the pedigree of The White Book which has seen numerous successful local editions in various common law jurisdictions, the Malaysian Civil Procedure 2018 provides you with the knowledge, information, practical insights and confidence to succeed in all areas of civil court work